Thymosin Beta 4 Is Involved in the Development of Electroacupuncture Tolerance - Wan, Juan; Ding, Yi; Nan, Sha; Zhang, Qiulin; Sun, Jinrui; Suo, Chuanguang; Ding, Mingxing (Frontiers in Cellular Neuroscience, 2019)
Background: Electroacupuncture (EA) tolerance, a negative therapeutic effect, is a gradual decline in antinociception because of its repeated or prolonged use. This study aims to explore the role of thymosin beta 4 (Tβ4), having neuro-protection properties, in EA tolerance (EAT). Methods: Rats were treated with EA once daily for eight consecutive days to establish EAT, effect of Tβ4 on the development of EAT was determined through microinjection of Tβ4 antibody and siRNA into the cerebroventricle. The mRNA and protein expression profiles of Tβ4, opioid peptides (enkephalin, dynorphin and endorphin), and anti-opioid peptides (cholecystokinin octapeptide, CCK-8 and orphanin FQ, OFQ), and mu opioid receptor (MOR) and CCK B receptor (CCKBR) in the brain areas (hypothalamus, thalamus, cortex, midbrain and medulla) were characterized after Tβ4 siRNA was administered. Results: Tβ4 levels were increased at day 1, 4, and 8 and negatively correlated with the changes of tail flick latency in all areas. Tβ4 antibody and siRNA postponed EAT. Tβ4 siRNA caused decreased Tβ4 levels in all areas, which resulted in increased enkephalin, dynorphin, endorphin and MOR levels in most measured areas during repeated EA, but unchanged OFQ, CCK-8, and CCKBR levels in most measured areas. Tβ4 levels were negatively correlated with enkephalin, dynorphin, endorphin, or MOR levels in all areas except medulla, while positively correlated with OFQ and CCK-8 levels in some areas. Conclusion: These results confirmed Tβ4 facilitates EAT probably through negatively changing endogenous opioid peptides and their receptors and positively influencing anti-opioid peptides in the central nervous system.